Current Issues in the Diagnostics and Treatment of Acute Appendicitis - Victorovich Garbuzenko, Dmitry (IntechOpen, 2018)
The book Current Issues in the Diagnostics and Treatment of Acute Appendicitis is devoted to the actual and in some cases controversial and unresolved problems associated with acute appendicitis, as well as peculiarities of its clinical picture, diagnosis, and treatment in children. The materials of the book will be of interest to anyone who considers emergency abdominal surgery their specialty.